Sentiment Analysis of YouTube Comments on Free Lunch Program Using Machine Learning - Bagus Satrio Pringgodani; Aji Supriyanto (Komunitas Dosen Indonesia, 2025)
In the digital era, social media has become a primary platform for the public to express opinions, including reactions to governmental initiatives such as Indonesia's